Kesalahan Ejaan dalam Teks Deskripsi Siswa Kelas XI SMA Negeri 3 Lhokseumawe - Cut Dinda Mifta; Syahriandi; Juni Ahyar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to describe spelling errors in descriptive texts of grade XI students of SMA Negeri 3 Lhokseumawe. This research method is descriptive qualitative. Data were collected using documentation and note-taking techniques. Data analysis techniques were carried out through several stages, namely collecting data samples and identifying errors, classifying data based on the type of spelling errors, and describing the forms of errors found. The results of the study indicate that many students still make spelling errors, such as errors in capitalization, writing basic words, redundant words, pronouns, prepositions, abbreviations and acronyms, period errors, and comma errors. These errors are caused by students' lack of accuracy and understanding in implementing Indonesian Spelling when writing. In this case, students must be given a better understanding of Indonesian Spelling. To overcome this problem, teachers have an important role in providing more intensive learning related to the implementation of Indonesian Spelling. One effort that can be done is to provide structured writing exercises, accompanied by direct feedback on spelling errors made by students. Furthermore, the use of digital learning media, such as spelling correction apps or interactive writing platforms, can help students improve their writing skills more effectively. With the right learning strategies, it is hoped that students will be able to understand spelling rules in depth and apply them correctly in every writing activity. Furthermore, students' writing skills also need to be honed through more varied activities, such as writing competitions, daily journals, or creative writing projects that require consistent application of spelling rules. Teachers can also implement a peer review method, where students correct each other's writing, thus creating collaborative learning that can increase language awareness.